Peningkatan Kepedulian Masyarakat Terhadap Kerajinan Melalui Pengolahan Barang Bekas - Ariza, Dida Rayhan; Ramadhanti, Ayona Wulan; Praseptian, Fidela Locita; Purnomo, Kristiana Felisia; Tyas, Woro Wiwaraning; Permana, Andhika Cahya; Saputri, Indah; Azhar, Thariq; Atmaja, Faisal; Rifai, Faizal; Fadillah, Roojil (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The community service program conducted by the service team of Universitas Muhammadiyah Yogyakarta aimed to raise awareness and enhance community skills in transforming used materials into valuable handicraft products. This program was implemented in Dusun Manggis, Kadipaten Village, Wonosobo Regency, in response to the low public awareness regarding non-organic waste management. Items such as plastic bottle caps, used plastic spoons, and waste paper are still often discarded despite their potential economic value when processed creatively. The program adopted a participatory approach through training, workshops, and mentoring that actively involved local residents, particularly the women from the Kelompok Wanita Tani (KWT). The implementation methods included field surveys, focus group discussions (FGDs), hands-on craft-making practices, and educational sessions on the importance of waste sorting and processing. The outcomes showed that the community began producing recycled crafts such as pencil holders, flower vases, and tissue boxes. This initiative not only improved environmental awareness but also created new economic opportunities for the villagers. Strong community engagement and the easy availability of raw materials in the surrounding area were key supporting factors in the program's success. It is expected that this initiative will have a long-term impact in fostering a culture of recycling and encouraging community-driven innovations for environmental sustainability.